Crimes cibernéticos - ANDRADE, Kayque Oliveira; GOMES, Luís Cauã Ferreira; PINHEIRO, Nicolas Ferreira; SILVESTRE, Paulo Henrik Alexandre; FELÍCIO, Rafaela Alves; SILVA, Vitória Ferreira da (172, 2023)
Crimes cibernéticos ou crimes virtuais, são práticas infratoras que atacam sites, perfis ou usuários. Ao longo dos anos muitos ataques virtuais surgiram, principalmente com o aumento da utilização da tecnologia e, para combater essa pratica diversas leis foram criadas. Embora tenha dificultado o acesso a cibercriminosos, o ato infrator continua em alta.

Cyber ​​crimes or virtual crimes are infringing practices that attack websites, profiles or users. Over the years, many cyber attacks have emerged, mainly with the increased use of technology and, to combat this practices several laws were created. Although it made access to cybercriminals, the offending act continues to be on the rise.
Keywords: Crime; Tecnologia; Gestão e Negócios